A Molecularly Engineered Zwitterionic Hydrogel with Strengthened Anti‐Polyelectrolyte Effect: from High‐Rate Solar Desalination to Efficient Electricity Generation - Zheng, Si Yu; Zhou, Jiahui; Si, Mengjie; Wang, Shuaibing; Zhu, Fengbo; Lin, Ji; Fu, Jimin; Zhang, Dong; Yang, Jintao (Advanced functional materials, 2023)
Polyzwitterionic hydrogel is an emerging material for solar‐driven water evaporation in saline environment due to its special anti‐polyelectrolyte effect, which is a promising approach to co‐generation of freshwater and electricity. However, the molecular impact on anti‐polyelectrolyte effect remains unclear, let alone to optimize the zwitterionic structure to promote water evaporation efficiency in high‐salinity brine. Herein, a molecularly engineered zwitterionic hydrogel is developed and the incorporated phenyl‐methylene‐imidazole motif greatly enhances the salt binding ability and strengthens anti‐polyelectrolyte effect, leading to boosted hydration, improved salt tolerance, ultra‐low evaporation enthalpy (almost half of traditional zwitterionic gel), and durable anti‐microbial ability in brine. Besides, gradient solar‐thermal network is penetrated to optimize water transport channel and heat confinement. The gel exhibits excellent evaporation rate of 3.17 kg m −2 h −1 in seawater, which is 1.6 times of that in water and such high efficiency could be maintained during 8 h continuous desalination, demonstrating outstanding salt tolerance. The high flux of ion stream can generate considerable voltage (321.3 mV) simultaneously. This work will bring new insights to the understanding of anti‐polyelectrolyte effect at molecular level and promote materials design for saline water evaporation.